Seashells and African Religious Rituals - Liu, Jun (International Journal of Social Sciences and Public Administration, 2025)
African religions have a long and influential history, and seashells are not only a form of currency in the lives of African people, but also play an important role in their religious lives, thus possessing the attribute of a medium connecting the secular and spiritual worlds of African people. This article mainly explores the role and significance of seashells in daily life and religious activities, thereby gaining a deeper understanding of local African religious phenomena and contributing to a deeper understanding of the inner world of African people.